The diagnostic accuracy using low-dose versus standard radiation dose CT in suspected acute appendicitis: prospective cohort study - Mäntyoja, Siiri (My University, 2022)
Acute appendicitis is the most common reason for acute abdominal pain and appendicectomy is one of the most common surgeries in the world. There are two types of acute appendicitis: uncomplicated and complicated. Uncomplicated acute appendicitis can be treated with antibiotics and the more severe form, complicated appendicitis, must be treated by appendicectomy. CT is the standard imaging for the diagnostic of acute appendicitis, and it can be used to differentiate between uncomplicated and complicated appendicitis. A major disadvantage in CT is the radiation exposure, especially as most of the patients with acute appendicitis are young adults. In this prospective single-center cohort study, we evaluated whether a lower radiation dose would affect the diagnostic accuracy of CT. Patients with suspected acute appendicitis in Turku University Hospital between April 2017 and November 2018 enrolled for the study if they met the inclusion criteria. Abdominal CT was performed on the patients: low-dose CT on patients with BMI under 30 kg/m2 and standard-dose CT on patients with BMI of 30 kg/m2 or higher. 856 patients (448 women, 408 men, median age 37) were enrolled in this study. 53 % of them underwent standard-dose CT and 47 % low-dose CT. The diagnostic accuracy was assessed by comparing on-call diagnosis to the final clinical diagnosis. There was no significant difference in low- and standard-dose abdominal CT in diagnosing acute appendicitis or in differentiating between uncomplicated and complicated acute appendicitis. The overall accuracy of CT in diagnosing acute appendicitis was 98.0 % in low-dose CT and 98.5 % in standard-dose CT. The accuracy in differentiating between uncomplicated and complicated acute appendicitis was 90.3 % in low-dose CT and 98.6 % in standard-dose CT. In subgroup analysis of patients with BMI under 30 kg/m2, the diagnostic accuracy of acute appendicitis was 98.2 % in low-dose CT and 98.6 % in standard dose CT (P=1.000), and differentiating between uncomplicated and complicated acute appendicitis was 89.8 % in low-dose CT and 88.4 % in standard dose CT (P=0.663). The median radiation dose was lower in low-dose CT than in standard dose groups (3 mSV vs. 7 mSV). In the subgroup analysis patients with BMI under 30kg/m2, the median radiation dose was significantly lower in the low-dose CT group than standard-dose CT group (3 mSV vs. 5 mSV, P<0,0001).
Keywords: Appendicitis, computed tomography, CT, low-dose CT, BMI